Super-rapid formation of a novel super-supramolecular hydrogel with excellent antimicrobial activity. (December 2021) - Guo, Shengzhu; Fan, Yanqing; Hong, Weiqian David; Liang, Jinfeng; Luo, Zhujun; Zheng, Wende; Li, Dongli; Gan, Lishe; Xu, Xuetao; Wu, Rihui; Jin, Jingwei; Zheng, Xi; et al.
Abstract: Smart hydrogels have received increasing attention for many applications. Herein, a novel supra-rapid formation supramolecular hydrogel with excellent antimicrobial activity was successfully constructed by GA-O-09, which was obtained by modification from none antimicrobial activity compound of 18 β -glycyrrhetinic acid (GA ). Interestingly, both GA-O-09 and the supra-rapid formation supramolecular hydrogel showed excellent performance in antimicrobial for Staphylococcus aureus (SA). Meanwhile, this supra-rapid formation supramolecular hydrogel also presented outstanding thermodynamics stability and showed performance in sustained released. This study implied that this super-rapid formation super-supramolecular GA-O-09 hydrogel showed excellent antimicrobial activity and had the potential for antibacterial material agent. Graphical abstract: Image 1 Highlights: A novel supra-rapidly supramolecular hydrogel with excellent antibacterial activity was generated. It is a novel and efficient approach to the design and development antimicrobial materials. The novel supra-rapidly supramolecular hydrogel showed good thermodynamic stability and controlled release property.